A review factors influencing the use of Computerised Accounting Systems (CAS) by Malaysian SMES in Malaysia - Jusoh, Najihah; Mohamed, Mazni; Afzainizam, Norzamziah; Ahmad, Hanyza (2018)
In an increasingly rapid world with technology and a borderless world, all companies need to adapt to the latest technology.Technology is made as one of the strategies to be competitive in the industry. One of the things to keep in mind is to use a computerized accounting system to ensure that reports are issued accurately, quickly and according to the established standards.Objective of this paper is to review the usage factors on Computerised Accounting Systems (CAS) among SME in Malaysia.The main purpose is to study the reason why SME refuse to use the CAS despite all of the benefit.The factors that been reviewed includes cost, selection and size of the business. The theory of Acceptance and Use of Technology (UTAUT) model factors through the concepts of perceived ease of use and perceived usefulness were also been reviewed.The review found that perceive ease of use, perceived usefulness, cost, selection and size of the business itself are among the factors that influence the SME decision in engaging CAS.